2020
DOI: 10.34119/bjhrv3n6-026
|View full text |Cite
|
Sign up to set email alerts
|

Análise do perfil epidemiológico dos praticantes de corrida de rua em Belém-PA / Analysis of the epidemiological profile of stretchers in Belém-PA

Abstract: Análise do perfil epidemiológico dos praticantes de corrida de rua em Belém-PA Analysis of the epidemiological profile of stretchers in Belém-PA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have been shown that in other traditional road races as well as Boston 10,12 , New York, Berlin and London marathons 8 as well as in the road races with shorter distances like 5 km, 10 km, and 15 km 13 which is the distance from the IRRSS. The dominance of Kenyan and Ethiopian athletes has been observed in indoor and outdoor competitions in all mainly sporting events 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have been shown that in other traditional road races as well as Boston 10,12 , New York, Berlin and London marathons 8 as well as in the road races with shorter distances like 5 km, 10 km, and 15 km 13 which is the distance from the IRRSS. The dominance of Kenyan and Ethiopian athletes has been observed in indoor and outdoor competitions in all mainly sporting events 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, road racing is extremely popular with thousands of practitioners in the country, an amount that has grown a lot since the 1970s 5 . The country currently has numerous runners and sporting events throughout the country 6,7 apparently with a greater participation of men 8 . In addition, Brazil produced runners that are part of the history of road racing like Ronaldo da Costa, who was once the world record holder for the marathon, Vanderlei Cordeiro de Lima, bronze medalist in the historic Olympics in Athens and Marilson Gomes dos Santos, two-time champion of the marathon in New York.…”
Section: Introductionmentioning
confidence: 99%